Standard methods for mechanical testing of welds (American Welding Society, 2016)
This specification establishes standard methods for mechanical testing of welds. The significance of each test, test apparatus, preparation of the test specimens, and the test procedure are described. Example test results sheets are provided. It is beyond the scope of this document to define the required mechanical properties or acceptance criteria for the weld metal. This standard makes sole use of U.S. Customary Units. Approximate mathematical equivalents in the International System of Units (SI) are provided for comparison in parentheses or in appropriate columns in tables and figures. Safety and health issues and concerns are beyond the scope of this standard and therefore are not addressed herein. Work performed in accordance with this standard may involve the use of materials that have been deemed hazardous, and may involve operations or equipment that may cause injury or death. This standard does not purport to address all safety and health risks that may be encountered.